EVALUATING DIAGNOSTIC VALUE OF MAGNETIC RESONANCE SPECTROSCOPY (MRS) FOR DIAGNOSIS OF MALIGNANT BREAST MASSES - ISLAM, ZU; FIRDOUS, A; ZAHRA, M; MALIK, MF; ZAFAR, Z; HASSAN, U (Biological and Clinical Sciences Research Journal, 2022)
To evaluate diagnostic value of magnetic resonance spectroscopy (MRS) for diagnosis of malignant breast masses. The study included 155 patients with breast lesions at Department of Radiology, CH & ICH Multan from January 2021 to June 2021.1.5 Tesla MR system was used for proton magnetic resonance spectroscopy (1H MRS). Consultant radiologist interpreted MR spectroscopy for distinguishing between benign and malignant lesions using histopathology as a gold standard. SPSS 20.0 was used for data analysis. Among 81 MRS positive cases, 76 had malignant lesions (True Positive) and 05 had no malignant lesion (False Positive) on histopathology. Among 74 MRS negative cases, 7 had malignancy on histopathology (False Negative), while 67 had no malignant lesion (True Negative) on histopathology. It was concluded that MRS has high sensitivity and accuracy for diagnosis of malignant breast lesions.